Social-cultural Change of Kusle People (Patan Pragya, 2023)
Change is a law of nature as nothing is static in this world. No new generation can ever be an exact replica of the old one. Social structure is never static as various internal as well as external social conditions and circumstances change the structure and function of Kusle society and culture. It can be observed that numerous research works have been carried out within Newari ethnic groups. However, the present study provides an ethnographic description and socio-cultural change of the Kusle people of Kirtipur. The study employed quantitative research, with an emphasis on exploratory and descriptive research designs, and purposive sampling from four distinct wards of the municipality. The study demonstrates that due to the cultural contact with other castes people as well as education, modernization and consciousness the Kusle’s social as well as cultural life is changing rapidly.